TERA FAEDAH DAN TERA ROHANI: NILAI PRAGMATIS SYAIR TERBITAN BALAI PUSTAKA SEBELUM PERANG - Zaenal Hakim (Pujangga: Jurnal Bahasa dan Sastra, 2015)
ABSTRACT This study revealed the terms of pragmatics in the poem Boedjang long way off (1927), daughters of Boerdah Poems (1931), and Poems Koerban Boeroe (tt). As a work laden with ethical values-moral, the three poems that express mandate of each will bebeneficial for the human spirit. Ethics-mandated moral is: SBJ encourage  mankind  to  be  forgiven,  SPB contains the   suggestionthat  humans  do  not do  treason, and  LCS suggested that applicable human patient. As a work of narrative, the poem presents all three conflicts caused by overly ambitious leaders in getting the treasure, throne, and women. As the substance of the story, the three elements have filled in beautifully for the flow calibration of each story. Key words: theory of pragmatic, ethical values; tera avail; and tera lovely ABSTRAK Penelitian ini mengungkapkan segi pragmatik dalam Syair Boedjang Djaoeh (1927), Syair Poeteri Boerdah (1931), danSyair Koerban Boeroe (t.t.). Sebagai karya yang sarat dengan nilai-nilai etika-moral, ketiga syair tersebut masing-masing mengungkapkan amanat yang akan berfaedah bagi rohani manusia. Etika-moral yang diamanatkan yaitu: SBJ menganjurkan manusia supaya bersikap memaafkan, SPB berisi anjuran supaya manusia tidak berbuat berkhianat, dan SKB menganjurkan supaya manusia berlaku sabar. Sebagai karya narasi, ketiga syair tersebut menyuguhkan konflik disebabkan para tokoh terlalu ambisius dalam mendapatkan harta, tahta, dan wanita. Sebagai substansi cerita, ketiga unsur tersebut sudah mengisi tera indah bagi alur masing-masing kisah. Kata kunci: teori pragmatik; nilai etika; tera faedah; dan tera indah